Prática de cirurgiões-dentistas em relação à prevenção, diagnóstico e tratamento das doenças periodontais na atenção primária à saúde - Mendes Júnior, Francisco Ivan Rodrigues (2024)
The Dental Surgeon (DC) plays an important role in the prevention, diagnosis and treatment of patients with Periodontal Diseases (PDs). The objective of this study was to evaluate, through a questionnaire, the characteristics and practices of Dental Surgeons (DCs) who worked in Primary Health Care (PHC) regarding the prevention, diagnosis and treatment of Periodontal Diseases (PDs), during the months of October and December 2021. 128 (one hundred and twenty-eight) CDs working in PHC in the state of Ceará in 2021 responded to a professional socioeconomic questionnaire and another nine-question questionnaire regarding their prevention practices, diagnosis and treatment in relation to periodontal diseases. The chi-square test was used to evaluate the association between the variables studied. The main results showed that 49.2% of those surveyed never used a periodontal probe for clinical periodontal diagnosis and only 7.1% carried out clinical diagnosis through periodontal examination. For 21.1%, periodontal diagnosis was not part of the clinical protocol of the health unit where they worked. For 63.3%, the severity of PDs was the main reason for referral to specialized care. Carrying out Oral Hygiene Instruction (OHI) for their patients was reported by 57% of respondents. This measure was significantly associated (p<0.05) with those who had worked in the profession for up to 6 years, with the fact that they were not public exams and did not have training in periodontics. The public servants had a lower frequency of using periodontal probes than the non-public servants (p<0.05). Respondents who were not trained in periodontics were more likely to refer patients due to "severity of PD" or "need for periodontal surgery" (p<0.05). These results point, in addition to the need for new studies, to the provision of continuing education courses in PHC with the aim of improving the practices of DCs in relation to the prevention, diagnosis and treatment of PDs.